Wound Morbidity in Minimally Invasive Anterior Component Separation Compared to Transversus Abdominis Release. Issue 2 (February 2017) - Parent, Brodie; Horn, Dara; Jacobson, Lauren; Petersen, Rebecca P.; Hinojosa, Marcelo; Yates, Robert; Wright, Andrew S.; Louie, Otway
Abstract : Background: Transversus abdominis release is a novel approach for myofascial advancement in ventral hernia repair and has been hypothesized to have lower rates of wound complication than anterior component separation. Methods: Patients who had a ventral hernia repair with either transversus abdominis release or minimally invasive anterior component separation from January of 2010 to January of 2016 were enrolled in this retrospective cohort study. Patient characteristics were collected through chart review. Primary outcomes were operative time and wound complications. Multiple linear/Poisson regression and Fisher's exact test were used to determine statistical significance. Results: Of 142 patients analyzed, 75 subjects underwent Butler minimally invasive anterior component separation and 67 underwent transversus abdominis release. There were no differences in baseline characteristics between groups, except that the anterior component separation group had more immunosuppressed patients (35 percent versus 19 percent). Median operative time for anterior component separation was 6.3 hours versus 6.1 hours for transversus abdominis release ( p = 0.6). Overall wound complications did not differ between the groups ( p = 0.5). Compared with anterior component separation, transversus abdominis release had a similar incidence of seroma/hematoma (relative risk, 0.9; 95 percent CI, 0.5 to 1.7), wound infection (relative risk, 1.1; 95 percent CI, 0.5 to 2.2), and mesh infection (relative risk, 0.7; 95 percent CI, 0.2 to 3.4). Hernia recurrence was 12 percent for anterior component separation and 6 percent for transversus abdominis release (relative risk, 0.6; 95 percent CI, 0.2 to 1.7). Reoperation was required in 19 percent of anterior component separation and 12 percent of transversus abdominis release subjects (relative risk, 0.5; 95 percent CI, 0.2 to 1.2). Conclusions: Transversus abdominis release patients had similar operative times, wound complications, reoperations, and hernia recurrences compared with Butler minimally invasive anterior component separation patients. This contemporary comparison helps inform operative decisions for reconstructive surgeons. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.